1999
DOI: 10.1038/sj.cr.7290025
|View full text |Cite
|
Sign up to set email alerts
|

NIH 3T3 cells malignantly transformed by mot-2 show inactivation and cytoplasmic sequestration of the p53 protein

Abstract: In previous studies we have reported that a high level of expression of mot-2 protein results in malignant transformation of NIH 3T3 cells as analyzed by anchorage independent growth and nude mice assays [Kaul et al., Oncogene, 17, 907-11, 1998]. Mot-2 was found to interact with tumor suppressor protein p53. The transient overexpression of mot-2 was inhibitory to transcriptional activation function of p53 [Wadhwa et al., J. Biol. Chem., 273, 29586-91, 1998]. We demonstrate here that mot-2 transfected stable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The previous works in our laboratory have been also shown an overexpression of p53 gene (data not shown). The other laboratory also demonstrated the alteration of related genes in malignant transformation of NIH 3T3 cells [16]. All there evidences indicated the alteration of expression of related genes.…”
Section: Discussionmentioning
confidence: 90%
“…The previous works in our laboratory have been also shown an overexpression of p53 gene (data not shown). The other laboratory also demonstrated the alteration of related genes in malignant transformation of NIH 3T3 cells [16]. All there evidences indicated the alteration of expression of related genes.…”
Section: Discussionmentioning
confidence: 90%
“…2E). To ascertain whether the apoptosis associated with MDM4 overexpression is not related to inhibition of growth arrest, we analyzed cell cycle profiles following growth factor withdrawal, a condition that causes a reversible growth arrest in the G 0 phase of the cell cycle in many cell types, including fibroblasts (41,42), and is mediated by p53 activity too (41,43).…”
Section: Stable Mdm4 Overexpression Does Not Affect P53 Levels Ormentioning
confidence: 99%
“…There is growing evidence that p53 sequestration in the cytoplasm may be a common mechanism of p53 inactivation. For example, both Mot-2 (Wadhwa et al 1999) and hepatitis B virus X protein (Elmore et al 1997) have been shown to physically interact with p53 and repress its transcriptional activity by sequestration in the cytoplasm. Estradiol inactivates p53 by intracellular redistribution (Molinari et al 2000).…”
Section: Discussionmentioning
confidence: 99%